2020
DOI: 10.1186/s13287-020-01725-4
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous infusion of human umbilical cord Wharton’s jelly-derived mesenchymal stem cells as a potential treatment for patients with COVID-19 pneumonia

Abstract: The novel coronavirus disease 2019 (COVID-19) has grown to be a global public health emergency since patients were first detected in Wuhan, China. Thus far, no specific drugs or vaccines are available to cure the patients with COVID-19 infection. The immune system and inflammation are proposed to play a central role in COVID-19 pathogenesis. Mesenchymal stem cells (MSCs) have been shown to possess a comprehensive powerful immunomodulatory function. Intravenous infusion of MSCs has shown promising results in CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
140
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(143 citation statements)
references
References 18 publications
3
140
0
Order By: Relevance
“…Encouragingly, Leng and colleagues reported that in the UC-MSCs treated group, the clinical parameters, including the oxygen saturation, inflammation and tissue injury biomarkers, and aspartic aminotransferase, were improved or normalized [220]. Moreover, a positive clinical outcome was also demonstrated in a severe COVID-19 patient treated with intravenous infusion of human umbilical cord Wharton's Jelly-derived MSCs [222]. These limited clinical data imply that MSCs exert their anti-inflammatory and immunomodulatory actions in COVID-19 patients.…”
Section: Anti-obesity-related Therapies: Potential Strategy For Combamentioning
confidence: 99%
“…Encouragingly, Leng and colleagues reported that in the UC-MSCs treated group, the clinical parameters, including the oxygen saturation, inflammation and tissue injury biomarkers, and aspartic aminotransferase, were improved or normalized [220]. Moreover, a positive clinical outcome was also demonstrated in a severe COVID-19 patient treated with intravenous infusion of human umbilical cord Wharton's Jelly-derived MSCs [222]. These limited clinical data imply that MSCs exert their anti-inflammatory and immunomodulatory actions in COVID-19 patients.…”
Section: Anti-obesity-related Therapies: Potential Strategy For Combamentioning
confidence: 99%
“…WJ-MSCs are becoming an interesting tool for allogenic transplantation in different kinds of disease, and also for COVID-19 complications [6][7][8]. Therefore, understanding the behavior of MSCs within the recipient tissues could be of great interest in assessing the safety of this kind of procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The use of WJ-MSCs is emerging in allogenic transplantation for different kinds of patients, due to their immunomodulatory properties [4,5]. Interestingly, in recent months, intravenous infusion of allogenic WJ-MSCs has been successfully used for the treatment of patients with COVID-19 pneumonia [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 is characterized by an acute respiratory illness caused by a new coronavirus type named as "severe acute respiratory syndrome coronavirus 2" (SARS-CoV-2). The COVID-19 is clinically heterogeneous, patients may be asymptomatic or have light, moderated, severe or critical symptoms [101][102][103][104].…”
Section: Msc Therapy In Viral Infections: Preclinical and Clinical Apmentioning
confidence: 99%
“…Therefore, therapy based on the use of hWJCs may be effective in the treatment of patients with COVID-19 [104].…”
Section: Msc Therapy In Viral Infections: Preclinical and Clinical Apmentioning
confidence: 99%